Search for nearly degenerate higgsinos via photon fusion with the semileptonic channel at the LHC - Hang Zhou; Ning Liu (Nuclear Physics B)
Electroweak scale higgsinos with a nearly degenerate spectrum in supersymmetric models are well-motivated, but generally less constrained at collider experiments as the decay products are often too soft to detect. Initial photon fusions alongside the collision of protons at the Large Hadron Collider (LHC) have drawn attention recently as a way to search for new physics with such kind of spectra. In this paper, we demonstrate a search strategy for chargino pair production from photon fusion pp→p(γγ→χ˜1+χ˜1−)p at the 13TeV LHC via the semileptonic decay channel, as a probe for the compressed spectra of higgsinos. Forward detectors make it possible to detect the outgoing protons after emitting the initial photons in these processes. We here provide simple event selections on missing energy and transverse momentum of leptons, which are effective enough to reach significant sensitivity. The chargino mass can be excluded at 95% C.L. up to about 295GeV with the mass difference Δm(χ˜1±,χ˜10) being only a few GeV with the integrated luminosity of 3ab−1. With a relatively small luminosity of 100fb−1, the 2σ exclusion bounds can as well exceed current experimental limits in the range of Δm=1∼2GeV, reaching over 190GeV for chargino mass.